تصغير خطوة الاستيفاء الداخلي الخطي باستخدام خوارزمية إقليدس - الشامي إبراهيم (Latakia University Journal -Engineering Sciences Series, 2019)
تبحث هذه الورقة في تحليل فكرة زيادة عدد الخطوات اللازمة لتوليد قطعة مستقيمة تصل بين نقطتين ذات قيم إحداثيات صحيحة دون أن يؤثر ذلك في سرعة التوليد، وزيادة عدد الخطوات يتم عن طريق تقسيم كل خطوة إلى خطوتين أو أكثر. يتم طرح خوارزمية جديدة تتصف بدقة توليد عالية ولا تتأثر سرعة التوليد فيها بزيادة عدد الخطوات. إذ يمكن إدخال عدد مرات مضاعفة عدد الخطوات لنحصل على الدقة التي نرغب. يستلزم تنفيذ الخوارزمية تطبيقها بمعالج مضمن يسمح بمضاعفة عدد عقد الشبكة لمستوي التوليد. This paper researches the analysis of the idea of increasing the number of the needed steps for straight generation of piece that links between two points of integers coordinates values without affecting generation speed. Increasing the number of steps is achieved by splitting each step to two or more. The new introduced algorithm is characterized by high accuracy of generation; its generation speed is not affected by increasing the number of steps, since it is possible to enter the number of times to double the number of steps to obtain the wanted accuracy. Algorithm requires its application to the Embedded Processor which allows doubling the number of network nodes for generating surface